Spectrum Sensing Utilizing Power Threshold and Artificial Intelligence in Cognitive Radio - Zainab Ali Abbood; Noor Alhuda F. Abbas; Basma Makki (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
The purpose of this paper was to take a preventative approach to predict the transmission status of the primary user (PU) on the white spectrum throughout the duration of the simulation. We intend to reduce the computational simulation budget to eliminate user interference by precise spectrum sensing handoff. We develop PU behaviors to use a time waiting estimate methodology that gives band occupancy time intervals. The proposed strategy may also lessen risks associated with flexible clients and adapt to changing channels. Real-time applications will use ANN range sharing, which reduces transmission delay, while high-throughput applications will use PTHD range sharing. Since noise as well as obscuring effects after each transmission plan, their proximity in the channel can influence range detection. This finding is in line with published investigations. Most range detection systems compare frequency test results with the operating channel's control scope thickness. The paper met design objectives by developing a noise-independent sensing methodology with proactive time estimation. The trial is accomplished with reduced cost and latency.